2005
DOI: 10.1016/j.mrfmmm.2004.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Stress responses and genetic variation in bacteria

Abstract: Under stressful conditions mechanisms that increase genetic variation can bestow a selective advantage. Bacteria have several stress responses that provide ways in which mutation rates can be increased. These include the SOS response, the general stress response, the heat-shock response, and the stringent response, all of which impact the regulation of error-prone polymerases. Adaptive mutation appears to be process by which cells can respond to selective pressure specifically by producing mutations. In Escher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
106
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(119 citation statements)
references
References 75 publications
3
106
0
5
Order By: Relevance
“…LexA levels fluctuate with pH variation as well as in ageing colonies. LexA inactivation during starvation or under oxidative stress induces polymerase Pol IV, which is expected to increase the error rate of DNA synthesis (Foster, 2005) and to result in multiple mutations during the transient hypermutation state (Tompkins et al, 2003) (Fig. 2).…”
Section: Role Of the Sos System?mentioning
confidence: 99%
“…LexA levels fluctuate with pH variation as well as in ageing colonies. LexA inactivation during starvation or under oxidative stress induces polymerase Pol IV, which is expected to increase the error rate of DNA synthesis (Foster, 2005) and to result in multiple mutations during the transient hypermutation state (Tompkins et al, 2003) (Fig. 2).…”
Section: Role Of the Sos System?mentioning
confidence: 99%
“…In reality, the frequency of sex generally depends on the condition of an individual, a pattern found broadly across both facultatively sexual prokaryotes and eukaryotes (Bell 1982). Individuals that are starved undergo sex at higher rates in a wide variety of organisms, including bacteria (Dubnau 1991;Redfield 1993;Jarmer et al 2002;Foster 2005), yeast (Kassir et al 1988;Mai and Breeden 2000), Chlamydomonas reinhardtii (Harris 1989), and daphnia (in combination with photoperiod and density cues; Kleiven et al 1992). Cells with DNA damage have also been shown to undergo sex at higher rates in viruses (Bernstein 1987), bacteria (Wojciechowski et al 1989), and yeast (Bernstein and Johns 1989).…”
mentioning
confidence: 99%
“…Under selection, 100 colonies appear from 10 8 plated cells over 6 days. This behavior suggested that selective stress might activate a mechanism to increase the general mutation rate (3)(4)(5). However, modeling indicated that such a mechanism would reduce long-term fitness (6,7).…”
mentioning
confidence: 99%